Glycyl-L-histidine crystal compound and preparation method thereof

By dissolving glycyl-L-histidine and precipitating crystals with alcohol solvents, a crystal compound with high stability was prepared, which solved the problem of poor stability of amorphous compounds and achieved the High purity maintenance under high temperature and humidity conditions.

CN119219728APending Publication Date: 2024-12-31ZHUHAI RUIDELIN BIOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310783802.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-28
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The amorphism of the existing glycyl-L-histidine compounds causes problems of wettability and stability, and a crystalline compound with high stability is urgently needed.

Method used

By dissolving glycyl-L-histidine in water and adding alcohol solvent, filtering and drying, crystals are precipitated by multiple cooling and multiple addition of alcohol solvents, glycine with characteristic X-ray powder diffraction patterns is prepared. Acet-L-histidine crystal compound.

Benefits of technology

The prepared glycyl-L-histidine crystal compound shows characteristic peaks in the X-ray powder diffraction pattern, which has higher stability, can maintain purity under high temperature, light and high humidity conditions, significantly improving the compound's Physical and chemical form stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004314601570000011
    Figure BDA0004314601570000011
  • Figure BDA0004314601570000021
    Figure BDA0004314601570000021
  • Figure BDA0004314601570000031
    Figure BDA0004314601570000031
Patent Text Reader

Abstract

The invention provides a glycyl-L-histidine crystal form compound. The X-ray powder diffraction pattern of the glycyl-L-histidine crystal form compound has characteristic peaks when the 2 theta value is 13.92 + / -0.2 degrees, 20.91 + / -0.2 degrees, 22.26 + / -0.2 degrees, 24.23 + / -0.2 degrees, 25.27 + / -0.2 degrees, 27.73 + / -0.2 degrees, 27.97 + / -0.2 degrees, 30.39 + / -0.2 degrees and 31.93 + / -0.2 degrees. A test result shows that compared with amorphous glycyl-L-histidine, the glycyl-L-histidine crystal form compound provided by the invention has higher stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of medical technology, and in particular to a glycyl-L-histidine crystalline compound and a preparation method thereof. Background Art

[0002] Glycyl-L-histidine (GH) is a dipeptide composed of two amino acids, glycine and L-histidine, with a chemical formula of C8H 12 N4O3, with a relative molecular mass of 212, has a chemical structure as shown below:

[0003]

[0004] GH is a key intermediate in the synthesis of Glycyl histidy lysine tripeptide (GHK). GHK is an active tripeptide that was isolated and purified from human plasma by the Pickart research team in 1973. GHK, as a complexing agent, can accelerate the migration of copper ions through the membrane, which is beneficial for the absorption of copper ions by the skin. Studies have shown that GHK has an inhibitory effect on Cu 2+ The ions show high affinity and the two can spontaneously combine to form GHK-Cu compounds.

[0005] Blue copper peptide is a compound formed by the combination of glycyl histidyl lysine tripeptide (GHK) and divalent copper ions. When it is dissolved in water, the solution is blue. Blue copper peptide has antioxidant properties. GHK can react with Cu 2+ ions form complexes, thus reducing the free Cu 2+ concentration, and there are many important enzymes in the human body and on the skin that require Cu 2+ These enzymes play a role in anti-oxidation and cellular respiration. 2+ At the same time, it can play a signaling function and affect cell metabolism.

[0006] As is known to all, different arrangements of compounds form different crystal forms, that is, a compound can have multiple crystal forms. Amorphous compounds have poor hygroscopicity and stability. Therefore, it is urgent to provide a crystalline compound of glycyl-L-histidine with good stability and no hygroscopicity. Summary of the invention

[0007] In view of this, the technical problem to be solved by the present invention is to provide a glycyl-L-histidine crystalline compound and a preparation method thereof, wherein the prepared glycyl-L-histidine crystalline compound has high stability.

[0008] The present invention provides a glycyl-L-histidine crystalline compound, the X-ray powder diffraction pattern of which is as follows: Figure 2 As shown, its X-ray powder diffraction pattern has characteristic peaks at 2θ values ​​of 13.92±0.2°, 20.91±0.2°, 22.26±0.2°, 24.23±0.2°, 25.27±0.2°, 27.73±0.2°, 27.97±0.2°, 30.39±0.2°, and 31.93±0.2°.

[0009] Preferably, the X-ray powder diffraction pattern of the glycyl-L-histidine crystalline compound has characteristic peaks at 2θ values ​​of 13.92±0.2°, 18.56±0.2°, 19.59±0.2°, 20.91±0.2°, 22.26±0.2°, 23.56±0.2°, 24.23±0.2°, 24.42±0.2°, 25.27±0.2°, 27.73±0.2°, 27.97±0.2°, 30.39±0.2°, 30.60±0.2°, and 31.93±0.2°.

[0010] Furthermore, the X-ray powder diffraction spectrum characteristics of the glycyl-L-histidine crystalline compound provided by the present invention are shown in Table 1, wherein the 2θ and interplanar spacing errors are ±0.2.

[0011] Table 1 X-ray powder (XRD) diffraction pattern of glycyl-L-histidine crystalline compound

[0012]

[0013]

[0014] Figure 1 The schematic diagram of the structure of the glycyl-L-histidine crystalline compound provided by the present invention.

[0015] Preferably, the bulk density of the glycyl-L-histidine crystalline compound is 0.592 g / cm 3 .

[0016] The present invention also provides a method for preparing the above-mentioned glycyl-L-histidine crystalline compound, comprising the following steps:

[0017] Glycyl-L-histidine is dissolved in water to obtain an aqueous solution, and then an alcohol solvent is added to the aqueous solution to precipitate crystals, which are filtered and dried to obtain a glycyl-L-histidine crystalline compound.

[0018] The present invention has no particular limitation on the source of the glycyl-L-histidine, and preferably the glycyl-L-histidine has a purity of 99% or more by HPLC. In the embodiments provided by the present invention, the glycyl-L-histidine can be purchased or prepared by a conventional method in the art.

[0019] Preferably, the concentration of the glycyl-L-histidine dissolved in water is 0.05 to 0.25 g / mL.

[0020] Preferably, the alcohol solvent is selected from one or more of methanol, ethanol, n-propanol, isobutanol and isoamyl alcohol.

[0021] Preferably, the volume ratio of the alcohol solvent to the aqueous solution is 0.2:1 to 1.2:1, more preferably 0.3:1 to 0.75:1.

[0022] Preferably, seed crystals are added to the aqueous solution, and the amount of the seed crystals added is preferably 0.5 wt% to 3 wt%, more preferably 0.5 wt% to 2 wt%.

[0023] The drop-adding rate of the seed crystals is preferably 50 to 400 μL / min.

[0024] Preferably, the temperature of the precipitated crystals is 0-25°C.

[0025] Preferably, the present invention uses a method of multiple cooling and multiple addition of alcohol solvent for crystallization.

[0026] Preferably, the first alcohol solvent is added to perform the first crystallization at room temperature, and then the second alcohol solvent is added to reduce the temperature to 5 to 10°C lower than the first crystallization temperature for the second crystallization, and then the third alcohol solvent is added to reduce the temperature to 5 to 10°C lower than the second crystallization temperature for the third crystallization.

[0027] The volume ratio of the first alcohol solvent, the second alcohol solvent and the third alcohol solvent is preferably (15-50):(10-25):(10-30).

[0028] The first crystallization time is preferably 1.5 to 2.5 hours.

[0029] The second crystallization time is preferably 2 to 6 hours.

[0030] The third crystallization time is preferably 1 to 12 hours.

[0031] Preferably, the crystallization is carried out under stirring, and the stirring rate is preferably 100-400 rpm.

[0032] The drying temperature is preferably 45°C to 80°C in vacuum drying.

[0033] Compared with the prior art, the present invention provides a glycyl-L-histidine crystalline compound, whose X-ray powder diffraction pattern has characteristic peaks at 2θ values ​​of 13.92±0.2°, 20.91±0.2°, 22.26±0.2°, 24.23±0.2°, 25.27±0.2°, 27.73±0.2°, 27.97±0.2°, 30.39±0.2°, and 31.93±0.2°. The test results show that compared with amorphous glycyl-L-histidine, the glycyl-L-histidine crystalline compound provided by the present invention has higher stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 Schematic diagram of the structure of the glycyl-L-histidine crystalline compound provided by the present invention;

[0035] Figure 2 is an X-ray powder diffraction (XRD) pattern of the glycyl-L-histidine crystalline compound provided by the present invention;

[0036] Figure 3 is an X-ray powder diffraction (XRD) pattern of the glycyl-L-histidine crystalline compound provided in the comparative example;

[0037] Figure 4 is a differential scanning calorimetry (DSC) diagram of the glycyl-L-histidine crystalline compound provided by the present invention;

[0038] Figure 5 is a thermogravimetric analysis (TGA) diagram of the glycyl-L-histidine crystalline compound provided by the present invention;

[0039] Figure 6 It is a microscope picture of the glycyl-L-histidine crystalline compound provided by the present invention. DETAILED DESCRIPTION

[0040] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in combination with the embodiments of the present invention. The described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] The following seed crystals are obtained by grinding a glycyl-L-histidine crystalline compound as a seed crystal.

[0042] Example 1

[0043] 7.5 g of glycyl-L-histidine solid was dissolved in pure water, the volume was adjusted to 50 mL, and the mixture was added to a 100 mL glass jacketed container. The stirring rate was 200 rpm, the seed addition amount was 1% of the mass of the glycyl-L-histidine solid, the drop rate was 50 μL / min, and 30% of the initial volume of ethanol (V / V) was added, and crystallization was first carried out at room temperature for 2 hours; the crystallization temperature was then cooled to 15°C, and 25% of the initial volume of ethanol (V / V) was added, and crystallization was carried out at 15°C for 5 hours; the crystallization temperature was then cooled to 10°C, and 20% of the initial volume of ethanol (V / V) was added, and crystallization was carried out at 10°C for 3 hours; the product was filtered, washed, and vacuum dried at 45°C to obtain 7.18 g of glycyl-L-histidine crystalline compound, with a yield of 95.7%, a content of 95.6%, and a purity of 99.65%.

[0044] Embodiment 2:

[0045] 2.5 g of glycyl-L-histidine solid was dissolved in pure water, the volume was adjusted to 50 mL, and the mixture was added into a 100 mL glass jacketed container. The stirring rate was 300 rpm, the seed addition amount was 0.5% of the mass of the glycyl-L-histidine solid, the drop rate was 150 μL / min, and 15% of the initial volume of methanol (V / V) was added, and crystallization was first carried out at room temperature for 1.5 h; the crystallization temperature was then cooled to 20° C., and 25% of the initial volume of methanol (V / V) was added, and crystallization was carried out at 20° C. for 2.5 h; the crystallization temperature was then cooled to 16° C., and 30% of the initial volume of methanol (V / V) was added, and crystallization was carried out at 16° C. for 1 h; the product was filtered, washed, and vacuum dried at 45° C. to obtain 1.88 g of glycyl-L-histidine crystalline compound, with a yield of 75.2%, a content of 85.2%, and a purity of 98.13%.

[0046] Embodiment 3:

[0047] 10g of glycyl-L-histidine solid was dissolved in pure water, the volume was adjusted to 50mL, and the mixture was added into a 100mL glass jacketed container. The stirring rate was 250rpm, the seed addition amount was 2% of the mass of the glycyl-L-histidine solid, the drop rate was 85μL / min, and then 10% of the initial volume of n-propanol (V / V) was added, and crystallization was first carried out at room temperature for 1h; then the crystallization temperature was cooled to 10°C, and 20% of the initial volume of n-propanol (V / V) was added, and crystallization was carried out at 10°C for 3.5h; the product was filtered, washed, and vacuum dried at 45°C to obtain 6.58g of glycyl-L-histidine crystalline compound, with a yield of 65.8%, a content of 87.6%, and a purity of 98.82%.

[0048] Embodiment 4:

[0049] 12.5g of glycyl-L-histidine solid was dissolved in pure water, the volume was adjusted to 50mL, and the mixture was added to a 100mL glass jacketed container. The stirring rate was 400rpm, the seed addition amount was 1.5% of the mass of the glycyl-L-histidine solid, the drop rate was 100μL / min, and 25% of the initial volume of isobutanol (V / V) was added, and crystallization was first carried out at room temperature for 2.5h; the crystallization temperature was then cooled to 18°C, and 20% of the initial volume of isobutanol (V / V) was added, and crystallization was carried out at 18°C ​​for 4h; the crystallization temperature was then cooled to 8°C, and 15% of the initial volume of isobutanol (V / V) was added, and crystallization was carried out at 8°C for 1.5h; the product was filtered, washed, and vacuum dried at 45°C to obtain 10.1g of glycyl-L-histidine crystalline compound with a yield of 80.8%, a content of 75.9%, and a purity of 93.6%.

[0050] Embodiment 5:

[0051] 5 g of glycyl-L-histidine solid was dissolved in pure water, the volume was adjusted to 50 mL, and the solution was added to a 100 mL glass jacketed container. The stirring rate was 280 rpm, the seed addition amount was 1.2% of the mass of the glycyl-L-histidine solid, the drop rate was 200 μL / min, and the solution was stirred at a stirring speed of 280 rpm for 10 min until the solid was completely dissolved and clarified, and then 50% of the initial volume of isoamyl alcohol (V / V) was added, and crystallization was first carried out at room temperature for 1.5 h; then the crystallization temperature was cooled to 10° C., and 10% of the initial volume of isoamyl alcohol (V / V) was added, and crystallization was carried out at 10° C. for 6 h; then 10% of the initial volume of isoamyl alcohol (V / V) was added, and crystallization was carried out at 10° C. for 12 h; the product was filtered, washed, and vacuum dried at 45° C. to obtain 4.1 g of glycyl-L-histidine crystalline compound, with a yield of 82.0%, a content of 82.9%, and a purity of 95.3%.

[0052] Comparative Example 1:

[0053] 15 g of glycyl-L-histidine solid was dissolved in 50 mL of pure water, and the dissolved sample was pre-frozen in a -80°C refrigerator, and after being frozen solid, it was placed in a freeze dryer at -40°C and freeze-dried for 48 hours; 1.44 g of glycyl-L-histidine was obtained, with a yield of 72.0%, a content of 80%, and a purity of 93.3%.

[0054] X-ray powder diffraction (XRD) test conditions: using PANalytical Empyrean X-ray powder diffractometer (PW3040 / 60, PANalytical Analytical Instruments Co., Ltd., the Netherlands), Cu-Kα radiation, wavelength The X-ray tube voltage was 45 kV, the X-ray tube current was 40 mA, the scanning range was 2-40° (2θ), the step length was 0.026°, and the step time was 36.465 s. The powder sample was flattened and placed on a micro sample tray for detection.

[0055] Test conditions for differential scanning calorimetry (DSC): A sealed pan device was used in a TA Instruments Q2000 differential scanning calorimeter. The sample (about 1-3 mg) was weighed in an aluminum pan, covered with a Tzero, and the sample was transferred to the instrument for measurement. The nitrogen gas flow in the sample chamber was 50 mL / min. Equilibrated at 25°C, heated from 25°C to 300°C at a heating rate of 10°C / min, and the data analysis software was TA Universal Analysis. In the DSC graph, the horizontal axis represents temperature (Temperature, °C), and the vertical axis represents the heat flow (Heat Flow, W / g) released per unit mass of the substance.

[0056] Thermogravimetric analysis (TGA) test conditions: TA Instruments Q500 thermogravimetric analyzer was used. 5-10 mg of sample was placed in a platinum crucible, the nitrogen purge gas flow in the sample chamber was 60 mL / min, and the temperature was heated from room temperature to 450°C at a heating rate of 10°C / min. The data was analyzed by TA Universal Analysis. In the TGA graph, the horizontal axis represents temperature (Temperature, °C), and the vertical axis represents the sample weight percentage (Weight, %).

[0057] Figure 2 is an X-ray powder diffraction (XRD) pattern of the glycyl-L-histidine crystalline compound prepared in Example 1 of the present invention; Figure 3 This is the X-ray powder diffraction (XRD) pattern of the glycyl-L-histidine crystalline compound prepared in Comparative Example 1; it can be seen that the glycyl-L-histidine compound obtained by freeze-drying is a non-crystalline compound.

[0058] The DSC test results of the glycyl-L-histidine crystal prepared by the method of the present invention are as follows: Figure 4 As shown, the DSC detection results show two endothermic peaks, whose peak values ​​are 97.4°C and 207.1°C, respectively, and no solvent peak.

[0059] Figure 5 This is a thermogravimetric analysis (TGA) diagram of the glycyl-L-histidine crystalline compound prepared in Example 1 of the present invention. It can be seen that when the temperature rises from 100°C to 150°C, the weight loss is 2.4%, and when the temperature rises from 150°C to 200°C, the weight loss is 6.8%. The decomposition temperature is 295.3°C, indicating that the crystalline structure is stable.

[0060] Figure 6 This is a microscope image of the glycyl-L-histidine crystalline compound prepared in Example 1 of the present invention. It can be seen that the crystalline form is a block crystal.

[0061] The crystalline form and amorphous form of the glycyl-L-histidine compound provided by the present invention were experimentally investigated for their influence on stability. The contents of the investigation are as follows: the crystalline form of the glycyl-L-histidine compound obtained in Example 1 and the amorphous glycyl-L-histidine compound prepared in Comparative Example 1 were placed in an open state, and the stability under high temperature (65°C ± 2°C), high humidity (93% RH), and light (4500Lx ± 500Lx) conditions was investigated. The investigation index was the sample purity, as shown in Table 2.

[0062] Table 2 Purity of glycyl-L-histidine compounds prepared in Example 1 and Comparative Example 1 under different conditions

[0063]

[0064]

[0065] The experimental results show that the new crystal form of the glycyl-L-histidine compound prepared by the present invention is more stable in physical and chemical form under the above-mentioned high temperature, light and high humidity conditions, while the purity of the amorphous glycyl-L-histidine compound decreases when placed under different conditions, and the purity of the compound decreases significantly after being placed for 10 days, 20 days and 30 days.

[0066] The glycyl-L-histidine obtained in Examples 2 to 6 was subjected to X-ray powder diffraction using the above method, and the results obtained were the same as those in Example 1, indicating that the obtained compound was the same crystalline compound.

[0067] The above embodiments are only used to help understand the method and core idea of ​​the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. A glycyl-L-histidine crystalline compound, characterized in that: Its X-ray powder diffraction pattern has characteristic peaks at 2θ values ​​of 13.92±0.2°, 20.91±0.2°, 22.26±0.2°, 24.23±0.2°, 25.27±0.2°, 27.73±0.2°, 27.97±0.2°, 30.39±0.2°, and 31.93±0.2°.

2. The glycyl-L-histidine crystalline compound according to claim 1, characterized in that Its X-ray powder diffraction pattern has characteristic peaks at 2θ values ​​of 13.92±0.2°, 18.56±0.2°, 19.59±0.2°, 20.91±0.2°, 22.26±0.2°, 23.56±0.2°, 24.23±0.2°, 24.42±0.2°, 25.27±0.2°, 27.73±0.2°, 27.97±0.2°, 30.39±0.2°, 30.60±0.2°, and 31.93±0.2°.

3. The method for preparing the glycyl-L-histidine crystalline compound according to any one of claims 1 to 2, characterized in that: The following steps are involved: Glycyl-L-histidine is dissolved in water to obtain an aqueous solution, and then an alcohol solvent is added to the aqueous solution to precipitate crystals, which are filtered and dried to obtain a glycyl-L-histidine crystalline compound.

4. The preparation method according to claim 3, characterized in that: The alcohol solvent is selected from one or more of methanol, ethanol, n-propanol, isobutanol and isoamyl alcohol.

5. The preparation method according to claim 3, characterized in that: The concentration of the glycyl-L-histidine dissolved in water is 0.05-0.25 g / mL.

6. The preparation method according to claim 3, characterized in that: Seed crystals are added into the aqueous solution, and the added amount of the seed crystals is 0.5 wt % to 3 wt %.

7. The preparation method according to claim 6, characterized in that: The seed crystal dropping rate is 50-400 μL / min.

8. The preparation method according to claim 3, characterized in that: The volume ratio of the alcohol solvent to the aqueous solution is 0.2:1 to 1.2:

1.

9. The preparation method according to claim 3, characterized in that: The temperature of the precipitated crystals is 0-25°C.

10. The preparation method according to claim 3, characterized in that: The crystallization is carried out under stirring, and the stirring rate is 100-400 rpm.